In Vitro Investigation of Novel Peptide Hydrogels for Enamel Remineralization - Codruta Sarosi; Alexandrina Muntean; Stanca Cuc; Ioan Petean; Sonia Balint; Marioara Moldovan; Aurel George Mohan (Gels)
This study investigates the microstructure of dental enamel following demineralization and re-mineralization processes, using DIAGNOdent scores and images obtained via scanning electron microscopy (SEM), atomic force microscopy (AFM), and microhardness (Vickers). The research evaluates the effects of two experimental hydrogels, Anti-Amelogenin isoform X (ABT260, S1) and Anti-Kallikrein L1 (K3014, S2), applied to demineralized enamel surfaces over periods of 14 and 21 days. The study involved 60 extracted teeth, free from cavities or other lesions, divided into four groups: a positive group (+), a negative group (−) and groups S1 and S2. The last three groups underwent demineralization with 37% phosphoric acid for 20 min. The negative group (−) was without remineralization treatment. The DIAGNOdent scores indicate that the S1 group treated with Anti-Amelogenin is more effective in remineralizing the enamel surface compared to the S2 group treated with Anti-Kallikrein. These findings were corroborated by SEM and AFM images, which revealed elongated hydroxyapatite (HAP) nanoparticles integrated into the demineralized structures. Demineralization reduced enamel microhardness to about 1/3 of a healthy one. Both tested hydrogels restored enamel hardness, with S1 being more effective than S2. Both peptides facilitated the interaction between the newly added minerals and residual protein binders on the enamel surface, thereby contributing to effective enamel restoration.